2006
DOI: 10.1309/qejbyt77ymtevj66
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Apparently False-Negative Digene Hybrid Capture 2 High-Risk HPV DNA Testing

Abstract: This study characterized cases with a negative high-risk Hybrid Capture 2 (HRHC2; Digene, Gaithersburg, MD) test result with concurrent or follow-up biopsy-confirmed high-grade cervical intraepithelial neoplasia (CIN 2/3). From 2,306 HRHC2 tests, 10 negative results were identified with CIN 2/3 (false-negative rate, 4.5%). The majority of the patients had abnormal colposcopic findings and high-grade squamous intraepithelial lesion (HSIL) shown by concurrent cytologic examination, although with few abnormal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…The majority of the latter lesions shed few abnormal cells, and they are small, as observed in this study, or focal, as reported recently by Jastania et al 19 Presumably, these lesions represent either early or regressing stages of cervical disease, which makes their clinical significance uncertain.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of the latter lesions shed few abnormal cells, and they are small, as observed in this study, or focal, as reported recently by Jastania et al 19 Presumably, these lesions represent either early or regressing stages of cervical disease, which makes their clinical significance uncertain.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, detection of HPV-35 was somewhat reduced when a mixture of probes for HPV-16, HPV-33 and HPV-35 were used, compared to a single probe for HPV-35. A BARCODE HPV assay has been developed for HPV genotyping, and was evaluated using only six (6,11,16,18, 45 and 51) of 45 different HPV types. (28) A serological multiplex method was reported for the detection of antibodies against HPV proteins based on in situpurified glutathione S-transferase fusion proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that primary human papillomavirus screening would have detected most, but not all, of these lesions. 27 More than half of the interval cancers in our series had other factors in the histories, often in addition to negative cytology. Low-grade cytology had rarely been managed as recommended and none of the cancers were in women with low-grade cytology followed by two or three negative tests.…”
Section: Discussionmentioning
confidence: 74%